Effect of heat stress on physiological responses in dairy cattle: A systematic review - Gayatri Gujar,; Monika Sodhi,; Vijay Kumar Choudhary,; Nampher Masharing,; Manish Tiwari,; Prince Vivek,; Manishi Mukesh, (Journal of Livestock Biodiversity, 2025)
The ever-changing climate as evidenced by the erratic weather phenomena globally and in India, poses a daunting challenge to the livestock industry. The already stretched resources of agriculture and livestock in the country is threatened due to unpredictable climate patterns, further worsening thermal stress on animals, especially dairy cows. Better understanding of eﬀect of climate on the animals will help in better management decisions and at the same time enhancing animal welfare. With this article, we tried to review the mechanisms associated with heat stress in cows and their associated physiological response.